Damage to endotracheal cuff inflation tube by harmonic scalpel in tonsillectomy leading to compromised airway - Azimee, Asfar; Thounaojam, Dinesh Singh (Journal of Society of Anesthesiologists of Nepal, 2016)
Use of harmonic scalpel has increased in the recent past for different surgical procedures. We report a case of damage to an endotracheal tube inflation line in a 47 year old female patient who underwent elective tonsillectomy due to harmonic scalpel. Pre-anaesthetic evaluation of the patient revealed no abnormalities. The patient’s trachea was intubated via nasal route with a cuffed north facing Ring, Adair and Elwyn tube of 7.0 mm internal diameter. The cuff was inflated after confirmation of tracheal placement of tube and pharyngeal packing was done. After 30 minutes of surgery, the bellows of the ventilator were collapsing. Suspecting a leak an attempt was made to inflate the cuff, which revealed high resistance in inflation tube. Surgeon was immediately asked to stop the surgery. Check laryngoscopy revealed damage to cuff inflation tube which was sealed by harmonic scalpel in semi-inflated condition. Anticipating that the tracheal extubation in that inflated position would result in vocal cord trauma, a 23 gauge spinal needle attached to 5ml syringe was introduced under direct laryngoscopic guidance. The cuff was punctured and air aspirated so as to deflate the cuff. The tube was taken out and was replaced. The surgery continued for next one hour, was uneventful and trachea extubated at completion.